Guidance provided by pharmacists to customers regarding to destination of unused household medications: disposal of household medications - Aparecida de Fatima Michelin; Neuza Alves Bonifácio; Walter Bertequini Nagata; Valéria Maria Savoya da Silva; Laura Emilia Michelin Gobbo; Katia Denise Saraiva Bresciani (BMC, 2023)
Abstract Background Discarding pharmaceuticals in the garbage or into the sewage system are still the most common methods in many countries. This study aims to investigate the guidance provided by pharmacists to customers on the disposal of unused and expired household medications in São Paulo State, Brazil. Method The study population consisted of 630 pharmacists from the State of São Paulo, who work in community pharmacies. They answered an online questionnaire with questions composed in three blocks: demographic, work, and academic information on the pharmacist; guidance about the disposal of household medications; and knowledge regarding the reverse logistics of these medications. An invitation to participate in the questionnaire was made via WhatsApp, individually and collectively. Inferential statistics were performed using the chi-square test and were considered significant when p < 0.05%. Results Among the participating pharmacists, the majority were women under 60 years old,56 (8.89%) stated that they never orient the customer regarding the disposal of unused and expired household medications, while 574 (91,12%) indicated that they almost provide guidance. The frequency with which they provided guidance was influenced by the number of years since graduation (p = 0.0047), the time they had worked in pharmacies and drugstores (p = 0.0007), and whether or not they had a graduate degree (p = 0.0181). Regarding the disposal of medications, among the 643 responses provided by the pharmacists,516 (80.25%) indicated that they oriented customers to return them to a pharmacy. Conclusion A small number of pharmacists always orient customers on the proper disposal that should be followed for unused and expired household medications, prioritizing their return to a pharmacy. In general, these pharmacists have longer periods of work experience and higher academic qualifications. Thus, it is important to increase knowledge through professional training and further education programs.